Assessment of platelet function on the routine coagulation analyzer Sysmex CS-2000i. (2nd January 2018) - Frère, Corinne; Kobayashi, Katsushi; Dunois, Claire; Amiral, Jean; Morange, Pierre-Emmanuel; Alessi, Marie-Christine
Abstract: Background: Light transmission aggregometry (LTA) is considered as the gold standard for testing platelet function in the setting of both platelet disorders suspicion and response to antiplatelet therapy evaluation. LTA requires however specialized equipment, substantial blood sample volumes, is technically challenging and time-consuming. Aim: To evaluate an automated platelet aggregation method performed on a routine coagulation analyzer Sysmex CS-2000i. Methods: 46 patients presenting a bleeding syndrome and 62 patients with acute coronary syndrome receiving dual antiplatelet therapy were studied in total. Platelet aggregations were performed on CS-2000i equipped with a dedicated software and on APACT-4004 (Elitech, France) as the reference instrument. Aggregation was measured by monitoring the changes in light absorbance occurring in response to ADP 2.5, 5 and 10µM, collagen 3.3 µg/mL, epinephrin 10µM, ristocetin 1.25 mg/mL and arachidonic acid 0.5 mg/mL in platelet rich plasma (PRP). PRP were tested simultaneously on both CS-2000i and APACT-4004 devices. Platelet stirred speed were 800 rpm for both instruments. Results: Significant correlations were observed between CS-2000i and LTA after all stimulations (p< 0.001). Patients presenting a bleeding syndrome had similar aggregation profiles with both methods. A single patient presented a severe platelet disorder (Glanzmann Thrombasthenia) and its PRP showed defective aggregation in response to all agonists except ristocetin with both instruments. Finally, the inter-agreement rates for CS-2000i and APACT-4004 to detect low responders to thienopyridines or aspirine were strong (weighted kappa> 0.70). Conclusion: Platelet aggregation on the routine coagulation analyzer CS-2000i is an easily accessible, handy, reliable, standardized, and rapid tool to assess platelet function which allows to skirt most of the LTA limitations.